2020
DOI: 10.1108/sajbs-03-2020-0060
|View full text |Cite
|
Sign up to set email alerts
|

Role of Big Five personality traits in regulatory-focused job crafting

Abstract: PurposeThis study examines the role of Big Five personality traits namely openness to experience, conscientiousness, extraversion, agreeableness and neuroticism in regulatory-focused job crafting, i.e. promotion- and prevention-focused job crafting and their inter-relationships.Design/methodology/approachSurvey data collected from 444 executives of Indian public sector energy companies were analysed using structural equation modelling.FindingsBig Five personality traits differentially influence individuals' wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
(160 reference statements)
1
7
0
2
Order By: Relevance
“…First, to the best of our knowledge, this is a pioneer study on EI in the SMEs of Pakistan to highlight the potential benefits of EI. In line with the RFT and prior research in the emerging markets (Sameer and Priyadarshi, 2020), the findings of this research suggest that PMF employees show developmental and growth values such as thriving, innovativeness and accomplishments. In contrast, PVF employees strive for safety needs and fulfill obligations rather than be involved in risky and innovative endeavors (Wallace et al , 2016).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…First, to the best of our knowledge, this is a pioneer study on EI in the SMEs of Pakistan to highlight the potential benefits of EI. In line with the RFT and prior research in the emerging markets (Sameer and Priyadarshi, 2020), the findings of this research suggest that PMF employees show developmental and growth values such as thriving, innovativeness and accomplishments. In contrast, PVF employees strive for safety needs and fulfill obligations rather than be involved in risky and innovative endeavors (Wallace et al , 2016).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, given the untapped research on RF and EI, little is explored about the underlying mechanisms of this relationship. By unearthing the mediating role of thriving on RF facets and EI, this study extends and contributes to three important knowledge streams – RF (Sameer and Priyadarshi, 2020), thriving (Kleine et al , 2019; Wallace et al , 2016) and EI (Gawke et al , 2018, 2019). This research enriches RFT by confirming thriving as a mediator between the positive (negative) relationship of PMF (PVF) and EI.…”
Section: Discussionmentioning
confidence: 65%
“…The selected organizations belong to both the public and private sectors in the Indian subcontinent. The study ensured that the organizations had the best human resource management (HRM) policies because prior studies have proposed that HRM is significant in enabling higher flexibility and job crafting as well as augmenting intrinsic motivation (Sameer and Priyadarshi, 2020). Researchers have suspected that the small public sector organizations might not have the best HRM policies (Aggarwal, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Job resources refer to the social, physical, organizational or psychological features of job that are useful for attaining work goals as well as in encouraging learning, individual progress and advancement. Job resources are associated with social support, positive organizational climate, autonomy, skill variety and career opportunities (Sameer and Priyadarshi, 2020). Past research has confirmed that job resources encourage work engagement instead of job demands (see Bakker and Demerouti, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we used demographic characteristics namely age, gender, marital status, education, work experience and job level were used as control variables in the study in line with prior studies (Robledo et al. , 2019; Sameer and Priyadarshi, 2021a, b). As one form of job crafting may affect the availability of job resources for pursuing other types of job crafting (Bakker and Demerouti, 2014), therefore, we also controlled for the effect of promotion-focused job crafting while assessing various relationships involving prevention-focused job crafting and vice-versa.…”
Section: Methodsmentioning
confidence: 99%